Internalisasi Nilai-Nilai Pancasila dan Nasionalisme Melalui Pendidikan Kewarganegaraan - Sulistyanto . (JURNAL CITRA WIDYA EDUKASI, 2013)
Historically, education has played an important role in encouraging nationalism among Indonesian people. Nowadays, education, especially citizenship education plays strategic and important roles in preserving, improving, and transforming state ideology and nationalism values to young generation. In globalization era, citizenship education has missions as political education, value education, nationalism education, democratic education, multicultural education, and conflict resolution education. Citizenship education must be interpreted in maximal interpretation that means teaches students to critically and analytically solve social problems and implement state ideology and nationalism values. Hence, citizenship education is not only taught as citizenship transmission but also taught as reflective inquiry. To do this, citizenship education is suggested to integrate direct and indirect approaches in value education, so that students are expected to be able in internalizing state ideology and nationalism values as their belief. Then, several principles of powerful teaching learning process should also color Indonesia school citizenship education.